Combining heat and altitude training - Racinais, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Originally in the form of terrestrial altitude, altitude exposure has evolved to the `living high - training low` model to maintain sea-level training intensity while promoting haematological adaptations (i.e. an increase in haemoglobin mass). More recently, repeated-sprints at altitude have also been shown to improve aerobic performance due to specific muscle adaptations. However, despite these refinements in altitude / hypoxic training methods, more and more athletes are looking for other training environments such as heat-acclimation. Two years ago, the number of AFL team going to hot ambient conditions for their pre-season training camp was even higher than the number of team going to altitude. This increasing interest for heat acclimation is linked to recent studies suggesting that this might improve performance in temperate conditions as well as at altitude via cross-acclimation pathways. Beyond comparing altitude and heat adaptations, it has been suggested that these two environments could induce complementary hematological adaptations; namely, an increase in hemoglobin mass and plasma volume. Recent studies have examined this concept in elite athletes. This is of particular interest for team-sport athletes as many of the physiological adaptations are triggered by the environmental conditions allowing saving time for tactical and technical training (Buchheit et al 2013). Of note, combining altitude and heat requires careful consideration as altitude adaptations require longer than those developing in the heat. The latest research has consequently combined the short-term muscle adaptations obtained by high-intensity training in hypoxia, with the short-term cardiovascular adaptations acquired by training in the heat. This lecture will highlight the most recent and relevant findings from elite athletes, and attempt to provide recommendations for crossacclimation training.